Protective effect of Selenium on the testes and spermatogenesis in acute and long-term cadmium treated male Swiss mice - Talib Hussen Ali; Tamara Walled Jahad (College of Education for Pure Sciences, 2012)
Abstract The protective effect of selenium chloride (SeCl2) against cadmium chloride (CdCl2), induced toxicity on sperms parameters, testes architecture and antioxidant enzymes in male Swiss mice was investigated. Intraperitoneal injection of CdCl2 (0.15 mg) dose in mice reduced total sperm count and significantly associated with increased sperm abnormality and death sperm percentage when compared with controls. The effect of Cd-treated mice showed a significant decrease in weight of testes and epididymides as compared with control groups. The degree of organ weight loss (testes and epididymides) were less severe in long-term treatment. Long-term exposure of both cadmium-injected mice had similar effect as acute exposure but with lower efficacy. Recovery period showed restoring effects in both exposure periods. The histopathological testes changes indicated by the reduction of seminiferous tubule diameter and testes architecture appearance due to the epithelial sloughing and elimination of germ cells were more pronounced at 72h/ Cd treatment. Substantially proves the ongoing damage effect of cadmium on developing germ cells. Long-term exposure of a batch of cadmium -injected mice had a similar effect as acute exposure but with lower efficacy. In addition, Intraperitoneal injection of CdCl2 (0.15 mg) also stimulate lipid peroxidation in testicular tissues, indicated by significant decrease in antioxidant enzymatic activity such as peroxidase and catalase in the experimental mice group. Administration of SeCl2 in combination with equal volume CdCl2 at the above mentioned doses led to partially organs weight resorted, elevated sperm count and reduction in the percentage of abnormal and dead sperm population along with significant increase in antioxidant enzymatic activities. The protective action and the antagonistic effect of Se at different periods against cadmium -induce toxicity are discussed.